2005
DOI: 10.1177/107424840501000408
|View full text |Cite
|
Sign up to set email alerts
|

Do All Patients With Coronary Artery Disease Benefit from Angiotensin Converting Enzyme Inhibitors?

Abstract: Cumulative evidence supports the use of angiotensin-converting enzyme (ACE) inhibitors for stable coronary artery disease in patients with and without heart failure. The dose and unique properties of ACE inhibitors, trial data, differences in trial design and demographics, may all contribute to variable responses in clinical outcomes. Pending direct comparator clinical trials between a tissue ACE inhibitor vs a plasma ACE inhibitor, evidence indicates that both ramipril and perindopril can be recommended for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The PEACE study population had a lower cardiovascular baseline risk (fewer patients with diabetes and high cardiovascular risk), lower arterial blood pressure, and LDL-cholesterol, and patients were treated more frequently with statins and antiplatelet drugs. Thus, as various editorials also pointed out, 125,126 what the PEACE study showed was that ACE inhibitors could be beneficial for patients with more risk factors (such as high serum lipids, diabetes mellitus) but may offer modest (to no) extra benefit for patients with low-risk factors or those that are already treated with statins and antiplatelet drugs. From the clinical studies, it can be concluded that aggressive risk factor modification in patients with atherosclerosis is still the primary goal and not all patients may need treatment with ACE inhibitors.…”
Section: Ace Inhibition In Patients With Coronary Artery Disease: CLImentioning
confidence: 99%
“…The PEACE study population had a lower cardiovascular baseline risk (fewer patients with diabetes and high cardiovascular risk), lower arterial blood pressure, and LDL-cholesterol, and patients were treated more frequently with statins and antiplatelet drugs. Thus, as various editorials also pointed out, 125,126 what the PEACE study showed was that ACE inhibitors could be beneficial for patients with more risk factors (such as high serum lipids, diabetes mellitus) but may offer modest (to no) extra benefit for patients with low-risk factors or those that are already treated with statins and antiplatelet drugs. From the clinical studies, it can be concluded that aggressive risk factor modification in patients with atherosclerosis is still the primary goal and not all patients may need treatment with ACE inhibitors.…”
Section: Ace Inhibition In Patients With Coronary Artery Disease: CLImentioning
confidence: 99%
“…In addition, the limited/lack of success of these orally administered therapeutic agents may be related to the differential tissue distribution and drug-specific pharmacodynamics that could limit their therapeutic concentrations in lung tissue. [17][18][19] These observations, taken together with the well-established hypertrophic actions and emerging role of proinflammatory signaling by Ang II and Ang II type 1 (AT 1 ) receptors, 2,20,21 suggest that the involvement of the RAS in PH should be re-examined. This view takes on an added relevance since the discovery of ACE2 as a new member of the RAS.…”
mentioning
confidence: 99%